THE EFFECTIVENESS OF SEMANTIC MAPPING STRATEGY TO IMPROVE STUDENTS` VOCABULARY MASTERY - Indriarti, Indriarti (ELT Forum: Journal of English Language Teaching, 2014)
The purpose of this study was to investigate the effectiveness of semantic mapping strategy to improve students` vocabulary mastery. The research design of this study was a quasi experimental design. The population was the seventh grade students of SMP Negeri 4 Batang in the academic year of 2013/2014. The samples consisted of 72 students, which divided into two groups, they were experimental group and control group. In order to collect data about studentsâ vocabulary mastery improvement and responses toward the implementation of semantic mapping strategy, the writer used vocabulary test and questionnaire. During the treatment, students in experimental group used semantic mapping strategy, while students in control group used wordlists strategy. In the pre test results, the mean score of the experimental group was 62,91 and the control group was 63,19. However, there was improvement in post test results. The analysis of the test result showed that the students` improvement of experimental group was higher than control group. In the post test, the mean score of the experimental group was 82,08 while the control group got 76,38. Based on statistical analysis by using t-test formula, indicated that the t-test was 3,29 and t-table was 1,99. It means that t-value was higher than t-table (3,29 >1,99). As a result, there is a significant difference in vocabulary achievement between the students who are taught by using semantic mapping strategy and those who are taught by using wordlists strategy. Based on the result of this study, the writer concluded that semantic mapping strategy is more effective to be implemented in teaching vocabulary to improve students` vocabulary mastery than wordlists strategy.